Awareness and Acceptability of Pre-Certified Halal Foods to Non-Muslim Students among Secondary Schools - Guiapal, Fareed M.; Usop, Annierah M.; Lumbu-an, Jenevieve D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Multiculturalism is increasingly shaping contemporary societies, yet food, a fundamental human necessity, often becomes a point of cultural and belief-based contention. The halal food industry has grown significantly, garnering support both locally and internationally. However, this burgeoning sector faces challenges related to establishing standardized regulations that acknowledge its role in nation-building and promote cultural diversity. This study aimed to assess the awareness and acceptance of pre-certified halal food among non-Muslim students across secondary schools in Lambayong, Sultan Kudarat. Employing a descriptive survey research design, the study utilized a researcher-developed questionnaire administered to 350 students selected through simple random sampling from seven identified schools in Lambayong, Sultan Kudarat. Findings indicated that despite Lambayong's diverse population, most respondents demonstrated awareness and positive perceptions of pre-certified halal food. However, some community elders and church leaders expressed reservations about allowing younger generations to consume such food. The study also observed that while many vendors and proprietors were Muslim, not all adhered to the practice of wearing hijab (for Muslim women), and some lacked necessary cooking equipment like gloves and hairnets. Furthermore, certain halal establishments were found to have inadequate sanitation and pest control measures. Ultimately, the study concluded that there exists a moderate relationship between respondents' awareness and their acceptance of halal food. Recommendations include schools collaborating with barangay and local government units to monitor the hygiene of nearby restaurants and canteens. Additionally, halal food establishments should prioritize enhancing their sanitation practices and hygiene protocols to ensure compliance and consumer confidence.